PERANCANGAN KAMPUS POLITEKNIK MULTIMEDIA GORONTALO DENGAN PENDEKATAN ARSITEKTUR BIOKLIMATIK - Lasang, Aswandi; Saman, Satar; Tallei, Vierta Ramlan (Universitas Negeri Gorontalo, 2024)
One of the efforts to increase human resources is the provision of appropriate and equitable education institutions across the region for the “implementation and improvement of knowledge, innovation as a literary form that has an objective of teaching the development of science to educate the nation’s next generation. The development of human growth is in line with the development of increasingly advanced technology such as the use of radio, PC, smartphone, web, press, television, and in industries such as house production, studio, programming, and other correspondence industry fields. Based on the study rationale, the scope of the study is on the learning place in the field of Multimedia. Currently, Gorontalo Province does not process a campus that specializes in Multimedia a lecture system of 30% theory and 70% practice whose contentst are adjusted to technological development and market need is expected to produce graduates who are competent in their respective fields. Those are as a consideration and adjustment to the function of the building and climatic conditions in the area. The Bioclimatic Architecture theme is utilized to respond to climate change, such as rain, heat, wind, and noise, and regulates the use of energy in buildings and materials that will be used.This study applied the library research method, while the data sources used are primary and secondary press release data, as well as data on the development of enthusiasts in the multimedia major in Gorontalo Province. The data obtained will be a primary reference in designing the Gorontalo Multimedia Polytechnic Campus. Salah satu upaya peningkatan sumber daya manusia adalah penyediaan lembaga pendidikan yang tepat dan merata di seluruh wilayah untuk “implementasi dan peningkatan ilmu pengetahuan, inovasi sebagai bentuk sastra yang bertujuan untuk mengajarkan pengembangan ilmu pengetahuan untuk mencerdaskan generasi penerus bangsa. Perkembangan pertumbuhan manusia sejalan dengan perkembangan teknologi yang semakin maju seperti penggunaan radio, PC, smartphone, web, pers, televisi, dan dalam industri seperti rumah produksi, studio, pemrograman, dan bidang industri korespondensi lainnya. Berdasarkan dasar pemikiran kajian, maka ruang lingkup kajian adalah pada tempat pembelajaran di bidang Multimedia. Saat ini Provinsi Gorontalo belum memiliki kampus peminatan multimedia dengan sistem perkuliahan 30% teori dan 70% praktik yang isinya disesuaikan dengan perkembangan teknologi dan kebutuhan pasar yang diharapkan dapat menghasilkan lulusan yang berkompeten di bidangnya masing-masing. Hal tersebut sebagai pertimbangan dan penyesuaian terhadap fungsi bangunan dan kondisi iklim di kawasan tersebut. Tema Arsitektur Bioklimatik dimanfaatkan untuk merespon perubahan iklim, seperti hujan, panas, angin, dan kebisingan, serta mengatur penggunaan energi pada bangunan dan material yang akan digunakan.Penelitian ini menggunakan metode penelitian deskriptif, sedangkan sumber data yang digunakan adalah data siaran pers primer dan sekunder, serta data perkembangan peminat jurusan multimedia di Provinsi Gorontalo. Data yang diperoleh akan menjadi acuan utama dalam perancangan Kampus Politeknik Multimedia Gorontalo.